2020
DOI: 10.1111/1471-0528.16277
|View full text |Cite
|
Sign up to set email alerts
|

Association between preconception paternal smoking and birth defects in offspring: evidence from the database of the National Free Preconception Health Examination Project in China

Abstract: Objective To clarify whether preconception paternal smoking has any adverse effects on the offspring. Design Prospective, population‐based study. Setting Preconception registry data from the National Free Preconception Health Examination Project. Population or sample Couples planning pregnancy, with complete information on preconception paternal smoking behaviour and pregnancy outcomes. Methods The effect of questionnaire‐based paternal smoking behaviour during preconception and pregnancy was assessed via logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…We have read the commentary by Horne et al 1 and agree with the authors: placebocontrolled surgical trials for superficial peritoneal endometriosis (SPE) are needed. Such designs are the gold standard of testing treatment efficacy for chronic pain 2 and without placebo-control, it is ultimately unknown whether women with SPE are subjected to repeated surgeries that are not only unnecessary but also potentially harmful.…”
Section: Sirmentioning
confidence: 57%
See 3 more Smart Citations
“…We have read the commentary by Horne et al 1 and agree with the authors: placebocontrolled surgical trials for superficial peritoneal endometriosis (SPE) are needed. Such designs are the gold standard of testing treatment efficacy for chronic pain 2 and without placebo-control, it is ultimately unknown whether women with SPE are subjected to repeated surgeries that are not only unnecessary but also potentially harmful.…”
Section: Sirmentioning
confidence: 57%
“…3 Further, placebo-controlled testing is required to ascertain that the therapeutic element or elements of surgery are responsible for the effect, particularly so when the effect is measured in patient-reported outcomes such as pain. 2,3 Second, while Horne et al 1 outline the problem of post-surgical pain in women with SPE, we believe more attention should be given to the women who develop neuropathic pain following surgery. Chronic post-surgical neuropathic pain (CPNP) is a serious complication that may amplify the patient's suffering, incur greater societal costs, and is difficult to treat.…”
Section: Sirmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the total response rate was over 70% and both the case and control groups had similar participation rates, which lessens this concern. To estimate potential selection bias, we compared paternal characteristics between controls and the general population in Guangdong province or China and found that most factors were comparable, especially paternal alcohol drinking rate (Wang et al, 2015), and paternal smoking rate (Zhou et al, 2020). To ensure complete ascertainment, we included all CHDs including live birth, fetal death, and still birth infants.…”
Section: Discussionmentioning
confidence: 99%